Lived experiences of single parent families in a high density suburb in Masvingo province, Zimbabwe. - Mupfumira, Isabel Makwara (Advances in Social Sciences Research Journal, 2017)
The study investigated lived experiences of single parent families of a high density suburb in Masvingo province, Zimbabwe. The qualitative approach utilising a descriptive survey was employed to study the phenomena. The population of the study comprised of female headed households. Households and respondents were sampled using convenience and purposive sampling. Data was collected through questionnaires, semi structured interviews and non participant observation. The data was presented and analysed in narrative form basing on the research questions and the themes which emerged. The findings from the study revealed that the extended family was an important factor in single parent families. The findings also revealed that fulfilment of family functions; physical, emotional, and psychological is sometimes a challenge in single parent families. The study established that to a greater extent the absence of one parent may contribute towards poor emotional and social development of the children. The study also established that the population studied experienced work overload, economic hardships and loneliness, especially the parents. The study recommends that single parents should form support groups where they share ideas on addressing challenges they face. The study also recommends community and extended family involvement in child rearing to provide role models in the place of the absent parent. Replica studies be conducted on single parents in other contexts to provide a holistic picture of single parenting and measures to minimise negative effects on children and parents.